High density catheter approach with liveview dynamic display improves procedural efficiency of atrial fibrillation ablation. (3rd October 2022) - Di Cori, A; Giannotti Santoro, M; Parollo, M; Della Volpe, S; Mazzocchetti, L; Barletta, V; Segreti, L; Viani, S; De Lucia, R; Canu, A; Grifoni, G; Soldati, E; et al.
Abstract: Introduction: PVI isolation confirmation after RF ablation is often time-consuming, especially in case of a single transeptal catheter approach into the left atrium. A novel Live View (LV) dynamic display mapping software, utilized in combination with the High Density (HD) Grid mapping catheter, allows to display beat-to-beat, dynamic regional mapping data. Purpose: We evaluated the feasibility and the procedural impact of a procedural left atrial workflow with a single transeptal-single HD catheter analysis, incorporating the LV Mapping Software for the assessment of PVI after ablation. Methods: Paroxysmal and persistent AF patients scheduled for AF ablation were prospectively enrolled. All patients underwent only PVI under LSI guidance (LSI between 5.5 and 6 anteriorly; LSI between 4.5 and 5 posteriorly) with a point by point strategy and an inter-lesion distance <6 mm. According to the HD mapping strategy used to confirm entrance block after first pass PVI, patients were divided in two groups. The HD-LV Group included patients mapped with the HD-LV software and the HD-standard mapping (SM) group included patients which received a conventional PVI validation with a static voltage/activation map. Left PVI was evaluated during distal coronary sinus pacing and right PVI during sinus rhythm. Exit block was also evaluated to confirm bidirectional block. Procedural efficiency parameters were compared between groups. Results: Forty-six patients with AF (58% paroxysmal) were prospectively enrolled. Twenty-five patients were included in the HD-LV Group and 21 in the HD-SM Group. PVI was successful in all patients. LV dynamic display analysis was feasible in all patients and allowed a simple and fast validation of right and left PVI, without the necessity of introducing a second catheter into the left atrium. The split screen modality, with a dynamic activation map on the left and a dynamic voltage map on the right, allowed to switch from CS pacing to sinus rhythm without the necessity of a remap. The overall mapping time (27±10 vs 37±14 min, p=0.006), total procedure time (138±33 vs 178±50 min, p=0.006) and fluoroscopy time (14±5.3 vs 23±11 min, p=0.006) were significantly lower in the HD-LV Group. No complication was seen in either group. Conclusions: A simplified clinical utilization of LiveView dynamic display with a single transeptal-single HD catheter approach is feasible and efficient after PVI, potentially simplifying the procedural workflow. A real-time dynamic mapping in daily practice may further enhance the clinical benefits of HD mapping during radiofrequency (RF) catheter ablation procedures. Funding Acknowledgement: Type of funding sources: None.